INVENTOR MEDIA TO OVERCOME COGNITIVE BARRIER ON INTEGRAL MATERIALS - Kartinah Kartinah; Dina Prasetyowati; Sugiyanti Sugiyanti (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
There are many causes for the emergence of barriers in learning; barriers caused by difficult materials, cognitive, heredity and didactic factors. To overcome this, the efforts that can be done is to facilitate students in learning mathematics through learning media. Purpose of this research is to develop media by utilizing the inventor application. This research was conducted at the Senior High School Lab School Semarang with the consideration that there had never been research related to barriers and media development. The development procedure adapts the model developed by Borg and Gall which consists of ten stages. However, in this study, it only reached the 5th stage, namely the main product revision. The results showed that the process and results of developing Inventor-based learning media to overcome barriers in the Integral material of high school students were valid. Students and teachers of mathematics subjects gave a good response. Learning mathematics with Inventor media to overcome cognitive barriers in Integral material for high school students produces effective learning based on the average score of class students who use Inventor beyond the minimum value so that the experimental class complete. The results of achievement in experiment classes are better than control classes.